Erkundung und Erforschung. Alexander von Humboldts Amerikareise - Knobloch, Eberhard (HiN - Alexander von Humboldt in the Net. International Review for Humboldt Studies, 2007)
Abstract In a similar way as Adalbert Stifter’s narrator in the novel “Late summer” A. v. Humboldt combined exploration with research, fondness for travelling with striving for findings during his travel through South America. Humboldt clearly indicated his double aim: to report on the visited countries, to collect facts in order to improve physical geography. The treatise consists of five sections: object, route, methods, results, evaluation. Zusammenfassung Ähnlich wie Adalbert Stifters Erzähler im Roman „Nachsommer“ verband A. v. Humboldt auf seiner Amerikareise Erkundung und Erforschung, Reiselust und Erkenntnisstreben. Humboldt hat sein doppeltes Ziel klar benannt: Bekanntmachung der besuchten Länder, Sammeln von Tatsachen zur Erweiterung der physikalischen Geographie. Der Aufsatz ist in fünf Abschnitte gegliedert: Anliegen, Route, Methoden, Ergebnisse, Auswertung.